Chemical control of Poa trivialis on New Zealand racetracks : a thesis presented in partial fulfilment of the requirements for the degree of Master of Applied Science at Massey University - Fleming, Philip Brian (Massey University, 1996)
Poa trivialis is a perennial grass weed commonly found in perennial ryegrass (Lolium perenne) racetrack swards throughout New Zealand. Its presence is undesirable as it does not tolerate high wear and is susceptible to dying out over the summer. Two pot trials at Massey University and one field trial carried out at the Awapuni racecourse were conducted during winter and spring 1995 to test the relative susceptibility of Poa trivialis and perennial ryegrass to a wide range of herbicides. A bioassay was also conducted to determine whether herbicide residues from the field trial could affect the germination of perennial ryegrass seed sown soon after treatment. Results showed that none of the chemicals at their chosen respective rates could completely remove Poa trivialis from a racetrack sward in the spring without some damage being caused to perennial ryegrass. Propyzamide and fenoxaprop at rates of 0.2 and 0.15 kg/ha respectively showed the most potential of the chemicals, severely damaging Poa trivialis (causing 50 to 75% reductions) with no adverse effect on perennial ryegrass 8 weeks after spraying. Propyzamide can also provide some control of Poa annua. Fenoxaprop was not improved by increasing the application rate or adding an oil. The performance of fenoxaprop was substantially reduced when applied with either MCPA or a picloram/triclopyr mix. Dalapon and asulam showed good potential to control Poa trivialis but at the high rates tested caused variable or harmful effects to perennial ryegrass. Ethofumesate and chlorpropham applied at rates of 2.0 and 2.5 kg/ha respectively gave inadequate control of Poa trivialis. None of the above herbicides, when used in the field trial resulted in residues which reduced the germination of perennial ryegrass seed sown 3 weeks after spraying. Herbicides tested in the pot trials which showed poor control of Poa trivialis were atrazine, dicamba, isoproturon/diflufenican, linuron, mecoprop, methabenzthiazuron, metsulfuron, pendimethalin, prometryne, thifensulfuron-methyl, triclopyr, and trinexapac-ethyl. Diuron applied at 2.6 kg/ha provided good control of Poa trivialis but caused significant damage to perennial ryegrass. It is concluded that an integrated management approach that incorporates both cultural and chemical techniques will be required to control Poa trivialis on New Zealand racetracks. Future trial work should be carried out on propyzamide applied at rates of 0.2-0.3 kg/ha in autumn to establish the most appropriate time of year to apply this herbicide.
Keywords: Herbicides; Weed control; Racetracks (Horse racing); Lolium perenne; New Zealand; Turfgrasses